STUDI KASUS KONSEP DIRI SISWA SEKOLAH DASAR - Budiarsih, Anita Putri; Zen, Ella Faridati (Jurnal Kajian Bimbingan dan Konseling, 2016)
This study aims to determine students' self concept elementary school level are often absent from school for more happy participated send goods by driving a truck, factors that affect the self-concept of students as well as learned behavior arising from the self-concept. This research is a qualitative case study type that includes the steps of: 1) Define the research questions, 2) Select the case and determine data gathering and analysis techniques, 3) Prepare to collect the data, 4) Collect data in the field, 5) Evaluate and analyze the data, and 6) Prepare the report. Data is collected using interview and observation techniques. Data were analyzed through the stages of data reduction, data presentation and conclusion. The results of this research are three self-concept of students that consist of: (a) I can drive and will be a driver, (b) I was the mainstay of the family that should help make a living, and (c) I'm not good at math. In addition, other results of this study are the factors that affect self-concept of students consists of factors originating from within the students, which is realized by comparing themselves with others, and the factors that come from outside in the form of the process of identifying the behavior of his grandfather by him , Also well-known as well as learned behavior that arise from student self-concept that includes ditching and passive when in class.